Comparison Between Elite and Subelite Swimmers on Dry Land and Tumble Turn Leg Extensor Force-Time Characteristics. Issue 6 (June 2018) - Jones, Julian V.; Pyne, David B.; Haff, G. Greg; Newton, Robert U.
Abstract : Abstract: Jones, JV, Pyne, DB, Haff, GG, and Newton, RU. Comparison between elite and subelite swimmers on dry land and tumble turn leg extensor force-time characteristics. J Strength Cond Res 32(6): 1762–1769, 2018—Elite swimmers demonstrate faster swimming turn times that are potentially a result of having better strength-power characteristics than subelite swimmers. We quantified differences between dry-land and swimming turn force-time characteristics in elite swimmers and subelite swimmers. Subelite (11 males: 17.4 ± 0.6 years; 10 females: 17.1 ± 0.6 years) and elite swimmers (15 male: 23.2 ± 2.3 years; 7 female: 21.6 ± 2.5 years) were tested in a cross-sectional design. All swimmers performed a body weight and loaded (20 kg females, 30 kg males) squat jump (SJ) on a portable force platform. On the same day, all swimmers completed swimming turn analyses using a force platform fixed within the pool wall. The magnitude of difference between groups was estimated using a standardized mean difference (effect size statistic). Elite male and female swimmers had superior swimming turn and dry-land force-time characteristics to subelite swimmers in all tests. The standardized mean differences between groups ranged from small to very large. The largest differences were SJ peak velocity unloaded (3.07 ± 1.0 m·s −1 males, 3.49 ± 2.29 m·s −1 females; standardized mean difference ± 90% confidence limits) and SJ peak power unloaded (2.59 ± 0.79 w male, 2.80 ± 1.64 w female) with elite male and female swimmers having a ∼25–50% higher performance than the subelites in both characteristics. Elite swimmers exhibit superior strength and power characteristics for the swimming turn compared with younger and less experienced swimmers. A well-planned and executed strength and conditioning program is needed for emerging swimmers to develop these qualities, as they transition to senior levels.